NIR-triggerable ROS-responsive cluster-bomb-like nanoplatform for enhanced tumor penetration, phototherapy efficiency and antitumor immunity. (November 2021) - Zhang, Yu; Du, Xiyou; Liu, Shangui; Yan, Huixian; Ji, Jianbo; Xi, Yanwei; Yang, Xiaoye; Zhai, Guangxi
Abstract: The restricted tumor penetration has been regarded as the Achilles' Heels of most nanomedicines, largely limiting their efficacy. To address this challenge, a cluster-bomb-like nanoplatform named CPIM is prepared, which for the first time combines size-transforming and transcytosis strategies, thus enhancing both passive and active transport. For passive diffusion, the "cluster-bomb" CPIM (135 nm) releases drug-loaded "bomblets" (IR780/1-methyl-tryptophan (1 MT) loaded PAMAM, <10 nm) in response to the high reactive-oxygen-species (ROS) concentration in tumor microenvironment (TME), which promotes intratumoral diffusion. Besides, IR780 generates ROS upon NIR irradiation and intensifies this responsiveness; therefore, there exists a NIR-triggered self-destructive behavior, rendering CPIM spatiotemporal controllability. For active transport, the nanoplatform is proven to be delivered via transcytosis with/without NIR irradiation. Regarding the anti-cancer performance, CPIM strengthens the photodynamic therapy (PDT)/photothermal therapy (PTT) activity of IR780 and IDO pathway inhibition effect of 1 MT, thus exhibiting a strongest inhibitory effect on primary tumor. CPIM also optimally induces immunogenic cell death, reverses the "cold" TME to a "hot" one and evokes systemic immune response, thus exerting an abscopal and anti-metastasis effects. In conclusion, this work provides a facile, simple yet effective strategy to enhance the tumor penetration, tumor-killing effect and antitumor immunity of nanomedicines.